Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1055/s-0035-1554907
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Stereotactic Radiosurgery and Radiation Therapy for the Treatment of Intracranial Chordomas

Abstract: Objective Chordomas are locally aggressive, highly recurrent tumors requiring adjuvant radiotherapy following resection for successful management. We retrospectively reviewed patients treated for intracranial chordomas with adjuvant stereotactic radiosurgery (SRS) and stereotactic radiation therapy (SRT). Methods A total of 57 patients underwent 83 treatments at the UCLA Medical Center between February 1990 and August 2011. Mean follow-up was 57.8 months. Mean tumor diameter was 3.36 cm. Overall, 8 and 34 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 57 publications
(74 reference statements)
0
21
0
Order By: Relevance
“…11,18 On univariate analysis, older patients had better PFS, which is incongruent with some studies which showed younger age is usually a positive prognostic factor. 20,[26][27][28] However, some publications showed no correlation with age 11,[29][30][31] while others showed older age had better outcomes. 32,33 In our analysis, this correlation did not stay significant on multivariate analysis and may be due to other confounding factors in our population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,18 On univariate analysis, older patients had better PFS, which is incongruent with some studies which showed younger age is usually a positive prognostic factor. 20,[26][27][28] However, some publications showed no correlation with age 11,[29][30][31] while others showed older age had better outcomes. 32,33 In our analysis, this correlation did not stay significant on multivariate analysis and may be due to other confounding factors in our population.…”
Section: Discussionmentioning
confidence: 99%
“…12,14,19 Radiation techniques for salvage therapies included GKRS, CKRS, proton therapy, carbon ion therapy, and LINAC-based SRS with recurrence rates ranging from 36 to 85%. 13,15,17,18,20 Bugoci et al from Kaiser, Los Angeles described novel therapy using molecular targets, including agents such as Gleevec and Dasatinib, with two out of three patients alive with stable disease after at least 30 months of therapy. 16 Attempts for meaningful comparisons between these different treatment algorithms are limited due to differences in patient population, tumor characteristics, and reported outcome measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using CRT at median doses of up to 60 Gy, a few studies report a local control at 5 years in the range of 17-41% [96][97][98][99]. New radiation techniques, including both IMRT and FSRT, which allow higher doses of radiation to the tumour while sparing more surrounding normal tissue, have been associated with better outcome (Table 4) [100,101]. Using IMRT with a median dose of 76 Gy given in 2 Gy per fraction in 24 patients, Sahgal et al [100] reported a 5-year survival and local control rates of 85.6 and 65.3%, respec-tively, at a median follow-up of 36 months.…”
Section: Chordoma and Chondrosarcomamentioning
confidence: 99%
“…Given these tumors' aggressiveness and the risk involved with a true total resection, the recurrence rate remains significant. The use of adjuvant radiation maximizes tumor control and neurological preservation [1]. Careful planning and reduction of dose delivered to adjacent critical structures are important considerations [3].…”
mentioning
confidence: 99%